A Needs Analysis survey in the EFL/ ESL class of a Greek Junior-High School and ICTs’ role - Papadaki, Aggeliki; Karagianni, Eleni; Driga, Anna Maria (Eximia, 2023)
The purpose of the particular paper is to develop and design a Needs Analysis questionnaire so as to examine the needs, wants and lacks of a specific group of learners, describe it and provide ideas for implementation in the EFL classroom. In the first part, there is a short literature review on Needs Analysis with reference to its significance in the EFL context and its components. In the second part, there is a description of the current teaching context, including learners’ profile, the curriculum, the coursebooks and the constraints. In the third part, there is a description of the particular questionnaire, while at the same time its rationale is presented. In the fourth part, there is an outline in flow chart format of all the steps in carrying out this needs analysis, from constructing the questionnaire to analyzing the final results. In the final part, there is a reflection on the significance of the particular needs analysis for the EFL classroom.